Pharmacological interventions for the treatment of obstructive sleep apnea syndrome - Liu, Jin; Yang, Xiaolan; Li, Guangcai; Liu, Peijun (Frontiers in Medicine, 2024)
Obstructive Sleep Apnea Syndrome (OSAS) affects 13-33% of males and 6-9% of females globally and poses significant treatment challenges, including poor adherence to Continuous Positive Airway Pressure (CPAP) and residual excessive sleepiness (RES). This review aims to elucidate the emerging interest in pharmacological treatments for OSAS, focusing on recent advancements in this area. A thorough analysis of extensive clinical trials involving various drugs, including selective dopamine reuptake inhibitors, selective norepinephrine inhibitors, combined antimuscarinic agents, and orexin agonists, was conducted.These trials focused on ameliorating respiratory metrics and enhancing sleep quality in individuals affected by OSAS. The studied pharmacological agents showed potential in improving primary outcomes, notably the apnea-hypopnea index (AHI) and the Epworth sleepiness scale (ESS). These improvements suggest enhanced sleep quality and symptom management in OSAS patients. With a deeper understanding of OSAS, pharmacological interventions are emerging as a promising direction for its effective management. This review provides a comprehensive overview of the current state of drug research in OSAS, highlighting the potential of these treatments in addressing the disorder's complex challenges.